2020
DOI: 10.3389/fphys.2020.00212
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MaltOBP1, a Minus-C Odorant-Binding Protein, From the Japanese Pine Sawyer Beetle, Monochamus alternatus Hope (Coleoptera: Cerambycidae)

Abstract: Insect Odorant-Binding Proteins (OBPs) play crucial roles in the discrimination, binding and transportation of odorants. Herein, the full-length cDNA sequence of Minus-C OBP1 (MaltOBP1) from the Japanese pine sawyer beetle, Monochamus alternatus, was cloned by 3 and 5 RACE-PCR and analyzed. The results showed that MaltOBP1 contains a 435 bp open reading frame (ORF) that encodes 144 amino acids, including a 21amino acid signal peptide at the N-terminus. The matured MaltOBP1 protein possesses a predicted molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Previous studies have proved that three plant volatiles, ocimene, nonanal and methyl palmitate, could elicite strong EAG responses in adult P. yasumatsui antennae ( Yan et al, 2017 ; Yan et al, 2020 ). However, our results indicated that PyasOBP2 exhibited strong and moderate binding affinity with ocimene (K i <10 μM) and nonanal (K i <20 μM), respectively, whereas it was incapable of binding with methyl palmitate (K i >20 μM), suggesting that an OBP could only bind with some specific odors during the process of insect chemoreception ( Zhang et al, 2020 ), and further studies on other OBPs from P. yasumatsui are needed to confirm this. Additionally, PyasOBP2 showed different binding affinities to some isomers, such as dipentene (K i <5 μM) and 3-carene (K i >20 μM), as well as ethyl butyrate (K i <5 μM) and butyl acetate (K i >20 μM), and it could not bind to some volatile ligands with more than 16 carbon atoms (such as methyl palmitate, methyl oleate and squalene), indicating that the size and structure of ligands, as well as their conformational changes, could affect the binding affinity for OBPs ( Sandler et al, 2000 ; Christina et al, 2017 ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Previous studies have proved that three plant volatiles, ocimene, nonanal and methyl palmitate, could elicite strong EAG responses in adult P. yasumatsui antennae ( Yan et al, 2017 ; Yan et al, 2020 ). However, our results indicated that PyasOBP2 exhibited strong and moderate binding affinity with ocimene (K i <10 μM) and nonanal (K i <20 μM), respectively, whereas it was incapable of binding with methyl palmitate (K i >20 μM), suggesting that an OBP could only bind with some specific odors during the process of insect chemoreception ( Zhang et al, 2020 ), and further studies on other OBPs from P. yasumatsui are needed to confirm this. Additionally, PyasOBP2 showed different binding affinities to some isomers, such as dipentene (K i <5 μM) and 3-carene (K i >20 μM), as well as ethyl butyrate (K i <5 μM) and butyl acetate (K i >20 μM), and it could not bind to some volatile ligands with more than 16 carbon atoms (such as methyl palmitate, methyl oleate and squalene), indicating that the size and structure of ligands, as well as their conformational changes, could affect the binding affinity for OBPs ( Sandler et al, 2000 ; Christina et al, 2017 ).…”
Section: Discussionmentioning
confidence: 76%
“…Since the first insect OBP was identified from Antheraea polyphemus ( Vogt and Riddiford, 1981 ), a large number of OBPs have been identified by using sequenced genomes and transcriptomes from several insect orders, including Diptera, Hymenoptera, Lepidoptera, Hemiptera, Coleoptera, and Orthoptera ( Jacquin-Joly et al, 2000 ; Northey et al, 2016 ; Wu et al, 2016 ; Pelosi et al, 2018 ; Venthur and Zhou, 2018 ). In recent years, an increasing number of studies involving the identification and function of OBP genes in insect species have demonstrated that most insect OBPs are highly expressed in antennae, indicating that OBPs play a key role in chemoreception ( Wang et al, 2019 ; Zhang et al, 2020 ). Moreover, OBPs are found to selectively bind to various volatiles emitted from host plants ( Deng et al, 2012 ; Ju et al, 2012 ; Cui et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the OBP18 of Helicoverpa assulta is mainly expressed in the antennae and involved in olfactory function [30]. The OBP3 of Bemisia tabaci is mainly expressed in the head and plays a role in recognizing host plant odor [31], whereas the OBP1 of Monochamus alternatus is highly expressed in the antennae and involved in host-seeking [32]. In addition, insect OBPs could also have other functions, when they are in body and not in antennae, suggesting a possible new function not related to chemoreception.…”
Section: Introductionmentioning
confidence: 99%
“…The most typical feature of OBP sequences are the six highly conserved cysteines that form three disulfide bridges to ensure a compact three-dimensional structure [ 24 , 25 ]. However, OBPs with fewer or more conserved cysteines have also been found [ 26 , 27 , 28 , 29 ]. OBPs can be divided into three distinct subfamilies: minus-C OBPs with four conserved cysteine residues; classic OBPs with six conserved cysteines, such as PBPs and general-odorant binding proteins (GOBPs); plus-C OBPs with eight conserved cysteines.…”
Section: Introductionmentioning
confidence: 99%